Applied Protein and Molecular Techniques for Characterization of B Cell Neoplasms in Horses - Badial, Peres R. [UNESP]; Tallmadge, Rebecca L.; Miller, Steven; Stokol, Tracy; Richards, Kristy; Borges, Alexandre S. [UNESP]; Felippe, M. Julia B. (Amer Soc Microbiology, 2015)
Mature B cell neoplasms cover a spectrum of diseases involving lymphoid tissues (lymphoma) or blood (leukemia), with an overlap between these two presentations. Previous studies describing equine lymphoid neoplasias have not included analyses of clonality using molecular techniques. The objective of this study was to use molecular techniques to advance the classification of B cell lymphoproliferative diseases in five adult equine patients with a rare condition of monoclonal gammopathy, B cell leukemia, and concurrent lymphadenopathy (lymphoma/leukemia). The B cell neoplasms were phenotypically characterized by gene and cell surface molecule expression, secreted immunoglobulin (Ig) isotype concentrations, Ig heavy-chain variable (IGHV) region domain sequencing, and spectratyping. All five patients had hyperglobulinemia due to IgG1 or IgG4/7 monoclonal gammopathy. Peripheral blood leukocyte immunophenotyping revealed high proportions of IgG1- or IgG4/7-positive cells and relative T cell lymphopenia. Most leukemic cells lacked the surface B cell markers CD19 and CD21. IGHG1 or IGHG4/7 gene expression was consistent with surface protein expression, and secreted isotype and Ig spectratyping revealed one dominant monoclonal peak. The mRNA expression of the B cell-associated developmental genes EBF1, PAX5, and CD19 was high compared to that of the plasma cell-associated marker CD38. Sequence analysis of the IGHV domain of leukemic cells revealed mutated Igs. In conclusion, the protein and molecular techniques used in this study identified neoplastic cells compatible with a developmental transition between B cell and plasma cell stages, and they can be used for the classification of equine B cell lymphoproliferative disease.